325 Functional analysis of macrophages to identify genetic markers associated with Johne's disease. (7th December 2018) - Bissonnette, N; Ariel, O; Brouard, J; Miglior, F; Ibeagha-Awemu, E
Abstract: Johne's disease (JD) is a contagious and chronic disease in ruminants caused by Mycobacterium avium ssp. paratuberculosis (MAP). It is known that MAP manipulates gut macrophages as a strategy to spare the host and ensure survival. Genetic variations in macrophages from susceptible cows were identified using a MAP infection assay. Primary monocyte-derived macrophages were exposed to live MAP for different times (1 h, 4 h, 8 h, 24 h, and uninfected) for collection of the full spectrum of differentially expressed genes.Transcriptomic analysis through next-generation sequencing (RNA-seq) was performed for 22 infectious (MAP-shedding) and 28 JD-negative cows. Using the GATK and joint-genotyping SNP caller, indels and SNPs were identified. DNA genotypes were also identified using a BovineSNP50 beadchip and imputed to high-density (HD) data. The variations totalled 1.36M high-quality genotypes. Functional variant effects were predicted using SnpEff, and tolerized genes were identified from the literature. Of the 814, 168 RNA-seq variants, 93, 279 were indels and 2, 435 are predicted to produce high functional effects on known genes, while only 33 DNA-HD genotypes were found in this category. A genome-wide association study identified two expression quantitative trait loci (eQTLs) on BTA4 and BTA11 at –log10 ( P ) ≥ 7. Interesting pathways (e.g. STAT transcription factor) deserve further investigation. Two genes among the tolerized genes were associated with significant SNPs. Interestingly, the encoded HMGC enzyme is higly expressed and might act as a flux-controlling point for cholesterol synthesis required for MAP survival and for cholesterol-enriched microdomains that act as a platform for the initiation of T-cell activation. In this study, we successfully identified eQTLs and regulatory pathways that distinguish between infected and JD-negative cows. While validation on a larger population is pending, integration of our findings into conventional programs for young sire selection and progeny testing might contribute to improve resistance to paratuberculosis in Canadian dairy herds.